Antifungal prescribing in neonates: Using national point prevalence survey data from Australia. (25th June 2021) - McMullan, Brendan J; Blyth, Christopher C; Jones, Cheryl A; Thursky, Karin A; Cooper, Celia; Spotswood, Naomi; James, Rodney; Konecny, Pamela
Abstract: We describe contemporary antifungal use in neonates, with point-prevalence survey data from the National Antimicrobial Prescribing Survey across Australian hospitals from 2014 to 2018. There were 247 antifungal prescriptions in 243 neonates in 20 hospitals, median age six days (range 0–27 days). In 219/247 prescriptions (89%) antifungals were prescribed as prophylaxis. Topical (oral) nystatin was the most frequently prescribed in 233/247 prescriptions (94%), followed by fluconazole 11/227 (4%), with substantial variation in dosing for both. Two of 243 neonates (0.8%) had invasive fungal infection. Nystatin use dominates current antifungal prescribing for Australian neonates, in contrast to other countries, and invasive fungal infection is rare. Lay summary: Novel nationwide surveillance found newborn infants in Australian hospitals commonly receive antifungal medications, mostly oral nystatin. This is given mainly to prevent rather than treat infection, which is rare. There is substantial unexplained variation in dosing of antifungal drugs nationally.